PENGARUH KOMUNIKASI CAMAT TERHADAP DISIPLIN PEGAWAI DI KANTOR CAMAT NGABANG KABUPATEN LANDAK - Teodolus Maturus E.42008047 (FISIP Universitas Tanjungpura Pontianak, 2013)
The title oh this research is “The Effect of Subdistrict Head Communication to EmployeeDiscipline at Ngabang Subdistrict Office”. This research aims to get an understanding andexplanation about the effect of Subdistrict Head communication to employee discipline at NgabangSubdistrict Office. This title is taken based on issue relating to employee discipline at NgabangSubdistrict Office, so the researcher assume that Subdistrict Head communication is a factor thateffect to employee discipline problem at Subdistrict Office. This research use quantitative methodswith form of associative research. The result of this research is Subdistrict Head communication hasan effect to employee discipline at Ngabang Subdistrict Office which is of 90,44%.Key words: Communication and Discipline